Tuberculous granuloma and cervical lymphadenopathy in an immunocompetent patient: a case report - Yong, Bernard Jonathan Christian; Sunaka, I. Wayan (International Journal of Advances in Medicine, 2022)
Tuberculosis (TB) is one of the top 10 infectious diseases causing mortality worldwide. In 2019, approximately 10 million people were diagnosed with TB, with 5.6 million men, 3.2 million women, and 1.2 million children. One of the hallmarks of the course of TB is tuberculous granuloma. In this study, we reported a case of TB granuloma and further workup to exclude other etiologies. A 52-year-old man presented with a complaint of a lump on his left neck. There was a history of prolonged productive cough, weight loss, and shortness of breath. Chest radiograph and FNAB of the lump suggested pulmonary TB while the rapid molecular test was negative. The patient was also suspected of malignancy; but the trans-thoracal biopsy did not reveal any malignant cells. The patient was eventually diagnosed with granuloma due to primary TB with cervical lymphadenopathy. Tuberculous granuloma is one of the most common pulmonary granulomas and a hallmark of the course of TB. It is characterized by the immune system forming an environment to control the spread of the infection. In cases of tuberculous granuloma with negative rapid molecular test, further investigations should be conducted to find evidence of TB infection. Activated TB granuloma can spread to the surrounding tissues or organs. A negative rapid molecular test result does not necessarily exclude TB in endemic regions; thus, further investigations such as CT scans or histopathological examination are required to find features of TB infection.